Inventory of Butterfly Species and Diversity (Lepidoptera) in Mataram City - Putu Eka Gunadi; Izzati, Lu’lu’atul Husna; Nurasmi, Intan; Houtave, Els (Yayasan Siti Widhatul Faeha, 2026)
Changes in the urban landscape can affect the structure of insect communities, including butterflies, which are sensitive to environmental conditions. This study aims to inventory butterfly species, analyze ecological indices, and examine how environmental factors influence butterfly communities in the city of Mataram. The method used was a field survey employing the time-search technique, with measurements of temperature, humidity, and light intensity, and analysis of the Shannon-Wiener diversity index, Margalef species richness, Pielou evenness, and Simpson's dominance. The results revealed 44 species from five families, with high diversity (H′ = 3.081), high species richness (R = 7.018), high evenness (E = 0.814), and low dominance (D = 0.077). Generalist species dominate the community, although a limited number of specialist species remain. The study's conclusions indicate that the butterfly community in Mataram City is relatively stable yet beginning to be affected by urban environmental pressures. The implications of this research underscore the importance of managing diverse, sustainable green open spaces to support butterfly conservation as an urban ecosystem bioindicator.